Nach Achtundsechzig. Krisen und Krisenbewusstsein in Deutschland und Frankreich in den 1970er Jahren - Möller, Horst (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte Sondernummer, 2013)
On both sides of the Rhine, the 1970s were characterized by intense social upheaval, economic shocks, and domestic and foreign policy uncertainties. This volume examines perceptions and consequences of the 1968 protest movement along with the impact of the 1973 oil crisis and the threat of terrorism as transnational phenomena.